Mechanistic insights into functional characteristics of native crotamine - Batista da Cunha, Daniel; Pupo Silvestrini, Ana Vitória; Gomes da Silva, Ana Carolina; Maria de Paula Estevam, Deborah [UNESP]; Pollettini, Flávia Lino [UNESP]; de Oliveira Navarro, Juliana; Alves, Armindo Antônio; Remédio Zeni Beretta, Ana Laura; Annichino Bizzacchi, Joyce M.; Pereira, Lilian Cristina [UNESP]; Mazzi, Maurício Ventura (Elsevier, 2018)
The chemical composition of snake venoms is a complex mixture of proteins and peptides that can be pharmacologically active. Crotamine, a cell-penetrating peptide, has been described to have antimicrobial properties and it exerts its effects by interacting selectively with different structures, inducing changes in the ion flow pattern and cellular responses. However, its real therapeutic potential is not yet fully known. Bearing in mind that crotamine is a promising molecule in therapeutics, this study investigated the action of purified molecule in three aspects: I) antibacterial action on different species of clinical interest, II) the effect of two different concentrations of the molecule on platelet aggregation, and III) its effects on isolated mitochondria. Crotamine was purified to homogeneity in a single step procedure using Heparin Sepharose. The molecular mass of the purified enzyme was 4881.4 Da, as determined by mass spectrometry. To assess antibacterial action, changes in the parameters of bacterial oxidative stress were determined. The peptide showed antibacterial activity on Escherichia coli (MIC: 2.0 μg/μL), Staphylococcus aureus (MIC: 8–16 μg/μL) and methicillin-resistant Staphylococcus aureus (MIC: 4.0–8.0 μg/μL), inducing bacterial death by lipid peroxidation and oxidation of target proteins, determined by thiobarbituric acid reactive substances and sulfhydryl groups, respectively. Crotamine induced increased platelet aggregation (IPA) at the two concentrations analyzed (0.1 and 1.4 μg/μL) compared to ADP-induced aggregation of PRP. Mitochondrial respiratory parameters and organelle structure assays were used to elucidate the action of the compound in this organelle. The exposure of mitochondria to crotamine caused a decrease in oxidative phosphorylation and changes in mitochondrial permeability, without causing damage in the mitochondrial redox state. Together, these results support the hypothesis that, besides the antimicrobial potential, crotamine acts on different molecular targets, inducing platelet aggregation and mitochondrial dysfunction.
Keywords: Antimicrobial; Crotalus durissus terrificus; Crotamine; Mitochondrial dysfunction; Platelet aggregation